A1.10 Human bone marrow-derived mesenchymal stromal cells strongly inhibit cytokine production by naive, memory and effector CD4+ and CD8+ T cells from rheumatoid arthritis patients, independently of disease activity status. (13th February 2015) - Pedrosa, M; Duarte, C; Laranjeira, P; Gomes, J; Ribeiro, T; Santos, F; Antunes, B; Pedreiro, S; Henriques, A; Martinho, A; Fardilha, M; Trindade, H; et al.
Abstract : Background and objectives: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterised by autoimmune activation leading to local and systemic consequences. Self-reactive T cells play a decisive role in the initiation and maintenance of the disease process. This disease course has been deeply modified by disease-modifying anti-rheumatic drugs that block pro-inflammatory cytokines, but still more than 1/3 of patients do not respond adequately to treatment. To overcome this limitation, mesenchymal stromal cells (MSC) based therapies have been recently explored. MSC are a population of adult non-hematopoietic stem cells with the ability to immunomodulate different cells of the immune system. The aim of this study was to verify the immunomodulatory activity of bone marrow (BM)-derived MSC on peripheral blood helper (Th) and cytotoxic T cells (Tc), distributed among their different functional compartments (naïve, central memory, effector memory and effector) from RA patients and healthy individuals. Materials and methods: To this purpose we preformed co-cultures with mononuclear cells and BM-MSC from 12 RA patients and 8 controls during 20 h in a ratio of 2:1 (MNC:BM-MSC). Then, T cells were activated with PMA and ionomycin for 4 h to induce cytokine production by T cells. The frequency of Th and Tc cells producing cytokines (IL-2, IFN-γ, TNF-α, IL-6, IL-17 and IL-9) among the different functional compartments was measured by flow cytometry. Moreover, IL-4, IL-10, TGF-β and CTLA-4 mRNA expression was assessed after cell sorting of CD4 + and CD8 + T cells. Results: BM-MSC clearly induced a decrease in the frequency of CD4 + and CD8 + T cells producing pro-inflammatory cytokines (for all the cytokines analysed) in all functional compartments and in both groups under study. However, the intensity of inhibition varied with the cytokine and the T cell functional compartment. Regarding the mRNA expression, in the presence of BM-MSC, we observed an increase of IL-4, IL-10, TGF-β and CTLA-4 in purified CD4 + T cells for both groups, although in a lower extent in RA patients. Likewise, BM-MSC induced an augment of mRNA levels of the abovementioned molecules in CD8 + T cells, although a more pronounced mRNA expression was observed in RA patients, excepting for IL-4, which expression decreased in both groups. Conclusions: Our data show that BM-MSC effectively inhibit pro-inflammatory cytokines production by Th and Tc in all functional compartments and increase the mRNA expression of anti-inflammatory molecules in both T cell subpopulations. These results support their potential utility in the treatment of autoimmune diseases.